The risk of thrombosis after acute-COVID-19 infection - Zuin, M (QJM, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) has been associated with coagulation dysfunction which predisposes patients to an increased risk of both venous and arterial thromboembolism, increasing the short-term morbidity and mortality. Current data evidenced that the rate of post-discharge thrombotic events in COVID-19 patients is lower compared to that observed during hospitalization. Rather than ‘true thrombotic events’, these complications seem more probably ‘immunothrombosis’ consequent to the recent infection. Unfortunately, the absence of data from randomized controlled trials, large prospective cohorts and ambulatory COVID-19 patients, left unresolved the question regarding the need of post-discharge thromboprophylaxis due to the absence of strong‐level recommendations.